A Comprehensive Review on Promising Phytopharmacological Applications of Chamomile Flower - Bhukta, Pallishree; Rath, Deepankar; Pattnaik, Gurudutta; Kar, Biswakanth; Kumar Ranajit, Santosh (Asian Journal of Chemistry, 2021)
Chamomile (Matricaria recutita L., Chamomilla recutita L., Matricaria chamomilla) is one of the most favoured single ingredient herbs. Chamomile tea is prepared by brewing the dried flower heads which has been used as traditional remedy. It is a crop introduced into India, mainly grown in Assam, Uttar Pradesh, Jammu & Kashmir states of India. The valuable unknown properties of this multipurpose herb should be explored to determine the therapeutic properties of its different parts, extracts, oils, etc. The flowers constitute many phenolic compounds like flavonoids, apigenin, patuletin, glucosides, luteolin and quercetin as main components. This herb is used as an antioxidant, antidepressant, antidiarrheal, antimicrobial, anti-inflammatory, antidiabetic, anticarcinogenic and hepatoprotective agents. In addition to that, it is also useful in treatment of gastrointestinal disorders, premenstrual syndrome, knee osteoarthritis andulcerative colitis. Matricaria Recutita chamomilla L. is used for both therapeutically and non-therapeutically around the globe that precipitate its remarkable worth. Chamomile contents of essential oils are widely used in aromatherapy and cosmetics. Most popular chamomile preparation is herbal tea which has been developed and consumed by more than one million cups per day across the globe. This review article briefs about the therapeutic efficiency along with phytology and cultivation techniques.